Evaluation of POSSUM Score for Outcome Prediction in Patients undergoing Major Gastrointestinal Surgery in Population of Central Nepal - Belbase, Narayan Prasad; Khatiwada, Sagar; Koirala, Nishnata; Prasad Upadhyay, Hari; Bhujel, Sushim; Shah, Bikash (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: The POSSUM score is one of the several risk scores to predict postoperative morbidity and mortality in the surgical domain.This study was designed to assess the validity of POSSUM scoring system in patients undergoing gastrointestinal surgeries in our setup and to analyse the outcome and compare the observed and expected values. Methods: An analytical cross sectional study was conducted among 100 patients in the Department of Surgical Gastroenterology after taking ethical approval from COMS-IRC. Data was analysed using SPSS -20 via descriptive and inferential statistical tools. p-value <0.05 was considered statistical significant. Results: Using POSSUM score the expected morbidity was 54% and mortality was 21.47%.The observed morbidity was 54% and mortality was 13%. The observed to expected (O: E) morbidity was 1.03 and mortality was 0.61 and there was no statistically significant difference between observed and expected value. The area under curve for POSSUM mortality score was 0.896 and the sensitivity and specificity of POSSUM score to predict mortality was 93.2 and 83.9 respectively. Conclusions: POSSUM score is a good mathematical tool in predicting morbidity and mortality in patients undergoing gastrointestinal surgeries. Keywords: gastrointestinal surgeries; central Nepal; expected morbidity and mortality; observed morbidity and mortality; POSSUM score.